Secondary mutant ALK-I1171s in pituitary metastases from a patient with ALK fusion-positive advanced lung adenocarcinoma: A case report and literature review - Han, Dan; Zhao, Kewei; Yang, Qin; Zhang, Liling; Fei, Shihong (Frontiers in Oncology, 2022)
Background: Pituitary metastasis accounts for a very low percentage of cases of brain metastasis from lung cancer, and there are uncertainties and challenges in diagnosis and treatment. We hope to shed some light on the diagnosis and treatment by reporting a case of ALK fusion mutation-positive lung cancer pituitary metastasis. Case presentation: We report a 48-year-old female patient with an initial diagnosis of stage IVB lung adenocarcinoma with ALK fusion. The patient developed headache, dizziness, hypopituitarism and hyperprolactinemia one year after treatment with crizotinib. Later, the patient underwent neurosurgical resection of the pituitary tumor and then symptomatic relief. Postoperative pathology suggested pituitary metastasis, and the next-generation gene sequencing conducted on the pituitary metastasis indicated that secondary drug resistance mutation ALK-I1171s occurred after the ALK fusion gene. Conclusion: In this article, we present a patient with suspected pituitary metastases with lung cancer. The progression to pituitary mass resection and next-generation gene sequencing of the pituitary metastasis are suggestive for further diagnosis and treatment.